Using the principles of multimodal analgesia as a component of Fast-Track surgery in practice - Ioffe, Oleksandr; Stetsenko, Oleksandr; Kryvopustov, Mykola; Tarasiuk, Tetiana; Tsiura, Yurii (Pain medicine, 2019)
Aim. To evaluate the effectiveness of reducing postoperative pain in the first days after surgery in accelerating postoperative recovery of patients and reducing the length of stay in hospital. Materials and methods. In the period from September 2011 to May 2019 we performed 569 scheduled surgeries using the Fasttrack surgery principles, including MMA. Depending on the type of surgery, we defined VAS pain impulses indicators and the average stay in hospital. Results. Analyzing the impulses of pain after laparoscopic cholecystectomy in the first postoperative day (POD) VAS level was 2.87 ± 0.74, the second POD – 2.01 ± 0.50 (p < 0.001). The average hospital stay was 1.72 days. In laparoscopic hernioplasty, the results of the study of the level of pain according to VAS were as follows: the first POD – 3.44 ± 0.67, the second POD – 2.06 ± 0.51 (p < 0.001). The average hospital stay was 1.43 days after surgery. Analyzing laparoscopic bariatric interventions and interventions on the large intestine the first POD level according to VAS was 4.24 ± 0.75 and 4.39 ± 0.84 respectively; the second POD – 3.48 ± 0.57 and 3.48 ± 0.77, the third POD – 2.79 ± 0.67 and 2.84 ± 0.69. When comparing the first and second PODs after bariatric interventions, the level of pain impulsion decreased to 3.48 ± 0.57 (p < 0.001), and to the third POD – to 2.79 ± 0.67 (p < 0.001). A similar tendency was observed after laparoscopic interventions on the large intestine: the second POD – the level of pain impulsion decreased 3.48 ± 0.77 (p < 0.001), the third POD – 2.84 ± 0.69 (p < 0.001). The average hospital stay was 4.99 ± 0.45 and 4.10 ± 0.60, respectively. Conclusions. The effectiveness of reducing postoperative pain in the first days after surgery directly affects the rate of recovery of the patient and the length of stay in hospital.